Barrier Factors That Affect Consumer Purchase Intention on Green Cosmetics Product: Applying Innovation Resistance Theory - Agrinita Dianti Puspitasari; Yeshika Alversia (School of Business, Bogor Agricultural University (SB-IPB), 2023)
Currently, green cosmetics are increasingly favored by consumers because of numerous benefits. In fact, there are a number of factors that hinder consumers intention to buy green cosmetics such as skepticism about green cosmetics, and greenwashing of brands. Therefore, this study aims to examine the factors that might hinder Indonesian consumers' intention to buy green cosmetic products. This study are using the role of personal and social norms as moderating variables to measure the significant impact that can reduce barriers to green cosmetic consumption. A total of 300 responses were collected as part of the quantitative study by distributing online questionnaires, followed by data processing using PLS-SEM. The research results show that usage barriers, value barriers and image barriers have a significant effect on restraining consumers' intention to buy green cosmetic products. However, the traditional barrier is influential as a determinant of the intention to buy green cosmetics. Furthermore, personal and social norms have a significant influence in weakening the relationship between risk barrier and intention to purchase green cosmetics. The results of this study may provide useful information to companies or brands that produce eco-friendly cosmetics on consumer occurring barrier factors that may hinder the purchase of cosmetics. green in Indonesia, so that the company can determine the right strategy to target its consumers. Keywords: green cosmetics product, purchase intention, personal norms, social norms, innovation resistance theory